The Effect of Service Quality and Delivery Accuracy on Customer Loyalty Through Customer Satisfaction (Case Study CV. Sarana Utama Cargo) - Sarifah, Zaydatus; Lestariningsih, Marsudi; Satrio, Budhi (International Journal of Business, Law, and Education, 2023)
This study aims to test and analyze the effect of service quality and delivery accuracy on customer loyalty through customer satisfaction as a case study on CV. Sarana Utama Cargo. The purpose in question is to test and analyze the effect of quality and accuracy of delivery on loyalty directly or indirectly through customer satisfaction.The methodology in this research is descriptive-quantitative using descriptive analysis and inferential statistics, namely, this research inferential statistical data analysis is measured using WarpPLS 5.0 software. The results of data analysis show that all indicators are said to be in this research model worthy of further processing until hypothesis testing. Based on the results of data analysis regarding direct and indirect effects, it shows that service quality and delivery accuracy have a significant effect on customer satisfaction, customer satisfaction has a significant effect on customer loyalty, and customer satisfaction has no mediating impact on service quality and customer loyalty while customer satisfaction has a mediating impact on delivery accuracy on customer loyalty. Customer satisfaction cannot mediate service quality on customer loyalty. This shows that the quality of services provided by the company is not a measure of customer satisfaction so it will have an impact on customer loyalty to the company's services. Delivery accuracy on customer loyalty is mediated by customer satisfaction. This shows the accuracy of shipping customer goods to their destination will make customers feel satisfied, so customers will be loyal to the services provided by CV. Sarana Utama Cargo. Service quality has a significant effect with a positive direction on customer loyalty. Customer satisfaction has a significant effect with a positive direction on customer loyalty. This shows that customers are satisfied with the services provided by the company, so that customers will be loyal to the company in this case CV. Sarana Utama Cargo. It is hoped that the results of this research can become a reference source for further research in discussing related problems. The population in this study are customers who are loyal to the company's CV. Sarana Utama Cargo used services more than one and so on. The sampling technique of this study was carried out by non-probability sampling method with purposive sampling technique with a total of 100 respondents.